Corrosion performance of epoxy/BTESPT/MAO coating on AZ31 alloy. (2nd January 2016) - Chen, M.-A.; Ou, Y.-C.; Yu, C.-Y.; Xiao, C.; Liu, S.-Y.
Abstract : To enhance the anticorrosion property of epoxy/microarc oxidation (MAO) coating on AZ31 magnesium alloy, bis-(triethoxysilylpropyl)tetrasulphide silane is chosen for surface pretreatment to the MAO coating. Fourier transform infrared, SEM, electrochemical tests and immersion test were used to investigate the structure and corrosion performance of the coatings. The results show that the anticorrosion property of the epoxy/MAO coating on AZ31 magnesium alloy can be improved effectively by the silane pretreatment to MAO coating.